Lipase epoxidation optimizing of Jatropha curcas oil using perlauric acid - Rafiee Moghaddam, Roshanak; Salimon, Jumat; Haron, Md. Jelas; Jahangirian, Hossein; Ismail, Mohd. Halim Shah; Hosseini, Soraya; Rezayi, Majid (Institute of Materials Physics, 2014)
As a novel renewable resource, Jatropha curcas seed oil with an iodine value of 103.57g/100g, and containing almost 44.7% oleic acid, 32.8% linoleic acid as the dominant fatty acids, 13.78% palmitic acid, 6.92% stearic acid and 0.71% palmitoleic acid was epoxidized using hydrogen peroxide as oxygen donor and lauric acid as an active oxygen carrier in the presence of immobilized Candida antarctica Lipase B. In the present work the effects of variables (reaction temperature, enzyme load, the mole ratio of H2O2: C=C bonds, lauric acid load and reaction time) on the oxygen oxirane content (OOC) of epoxidized Jatropha curcas were investigated. The process was optimized for the enzymatic epoxidation of Jatropha oil, with the theoretical maximum OOC equal to 6.13%. The OOC of epoxidized Jatropha oil was 5.67% and a percentage relative conversion to oxirane(RCO) was 93.64 % under the following conditions:50C (temperature), 7% enzyme load (relative to the weight of Jatropha of oil), 3.5:1 mol ratio of H2O2: C=C bonds, 23% lauric acid load (relative to the weight of Jatropha oil) and 7.5 h (reaction time).